Chinese parents’ intention to vaccinate their 0–5-year-old children with the EV-71 vaccine against hand, foot, and mouth disease and willingness-to-pay - Cheng, Lu; Zhong, Sumei; Xu, Xiaonan; Li, Junrong; Xie, Fangqin; Lin, Yulan; Zhang, Dongjuan (Frontiers in Public Health, 2024)
Background: This study aims to determine the intention and willingness-to-pay (WTP) of Chinese parents/guardians to vaccinate their children with the EV-71 vaccine. Knowledge levels about hand, foot, and mouth disease (HFMD) and the EV-71 vaccine were also investigated. Methods: A cross-sectional, self-administered online survey was conducted during November 2022 and March 2023. A stratified multi-stage random sampling method was used to recruit parents/guardians of children aged 0-5 years in Southeastern China. Results: A total of 3,626 complete responses were received. The mean knowledge score of HFMD was 9.99 (±4.23) out of a total of 14 points. The majority of participants reported a somewhat willing intent (58.8%), followed by an extremely willing intent (28.9%). Participants who did not consider the EV-71 vaccine expensive (OR=2.94, 95%CI 2.45–3.53), perceived that EV-71 vaccine is effective (OR=2.73, 95%CI 1.52–4.90), and high knowledge level of HFMD (OR=1.90, 95%CI 1.57–2.29) had the highest significant odds of extremely willing intent to vaccinate their child with EV-71 vaccine. The median (interquartile range [IQR]) of WTP for EV-71 vaccine was CNY¥200/US28 (IQR CNY¥100–400/USD14–56). The highest marginal WTP for the vaccine was mainly influenced by the perceived high cost of vaccine. Those participants who did not consider the EV-71 vaccine expensive had more than 10 times higher odds to vaccinate their child (OR=10.86, 95%CI 8.49–13.88). Perceived susceptibility, perceived benefits, and perceived barriers were also significant influencing factors of the highest marginal WTP. Conclusion: The findings demonstrate the importance of improving health promotion and reducing the barriers to EV-71 vaccination. It is important to improve health promotion and reduce the barriers to EV-71 vaccination.